2017
DOI: 10.1021/acs.macromol.7b01964
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Poly(substituted methylene)s Prepared by Pd-Initiated Polymerization of Fluorine-Containing Alkyl and Phenyl Diazoacetates: Their Unique Solubility and Postpolymerization Modification

Abstract: Pd-initiated polymerization of fluorine (F)-containing alkyl and phenyl diazoacetates is described. Polymerization of 2,2,2-trifluoroethyl diazoacetate [Et­(CF3)­DA] with π-allylPdCl afforded a C–C main chain polymer bearing a 2,2,2-trifluoro­ethoxycarbonyl group on each main chain carbon atom. The polymer showed upper critical solution temperature (UCST)-type phase separation in multiple common organic solvents with differing polarities. Although homopolymerization of 3,3,4,4,5,5,6,6,6-nonafluorohexyl diazoac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Comparison of 1 and ( π -allyl)palladium acetate dimer 2729 (2), as well as ( π -allyl)palladium methacrylate dimer (3) in the polymerization of EDA and 2,2,2-trifluoroethyl diazoacetate (TFEDA) 30 under equivalent conditions revealed that, as anticipated, in the presence of 2 and 3, both monomers were polymerized in nearly quantitative yield, while 1 afforded low yields of corresponding polycarbenes and mostly produced maleate and fumarate esters (Figure 2A). Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) confirmed that the polymer chains were virtually uniformly carboxylate-initiated and hydrogen-terminated, the latter presumably generated through protodepalladation upon exposure to air (Figure 2B, Supporting Information (SI), Figures S1 and S2).…”
mentioning
confidence: 99%
“…Comparison of 1 and ( π -allyl)palladium acetate dimer 2729 (2), as well as ( π -allyl)palladium methacrylate dimer (3) in the polymerization of EDA and 2,2,2-trifluoroethyl diazoacetate (TFEDA) 30 under equivalent conditions revealed that, as anticipated, in the presence of 2 and 3, both monomers were polymerized in nearly quantitative yield, while 1 afforded low yields of corresponding polycarbenes and mostly produced maleate and fumarate esters (Figure 2A). Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) confirmed that the polymer chains were virtually uniformly carboxylate-initiated and hydrogen-terminated, the latter presumably generated through protodepalladation upon exposure to air (Figure 2B, Supporting Information (SI), Figures S1 and S2).…”
mentioning
confidence: 99%
“…[ 26,27 ] Nonetheless, although well established in the organic chemistry toolbox, such reactions have not been applied for functionalization of polymer surfaces, and rarely for the homogeneous post‐functionalization of synthetic polymers. [ 28,29 ] In the latter case, this may be due to the high molecular weight nature of the polymer reactant, which can pose significant synthetic challenges, including highly diluted reaction condition, limited conversion, and problems in the purification and characterization processes. [ 30 ] We anticipate that such difficulties may be avoided in the surface modification because the reaction occurs in the heterogeneous phase between a solid substrate and the reactants in the solution.…”
Section: Figurementioning
confidence: 99%
“…One exception to the above rule might be the substituted polymethylene (PolyC 1 ) discussed in the Introduction although its solubility in fluorinated solvents has not been reported yet. 5 A possible partial explanation for this observation might be related to the fact that 4 has two lateral fluorinated chains on a small repeat unit, thus generating a highly fluorine-rich polymers (e.g., the added thiol chains makes 82 wt-% of the total mass in 4 while the original 3a backbone contributes only to the remaining 18 wt-%). In addition, the location of the ester groups on the polymer chain, with two lateral chains protruding from the backbone on every third carbon alongside the backbone (see Scheme 1c), generates a very high density of fluorinated grafts, which might "hide" the central chain and reinforce the polytetrafluoroethylene-like character of the polymer, including its low solubility.…”
Section: Synthesis Of Fluorinated Polymermentioning
confidence: 99%
“…A very recent contribution by the Ihara group looked at carbon-chain polymers substituted on every single carbon by ester bearing fluorinated side chains, providing evidences not only that these extremely crowded polymers were accessible but also that they exhibit solubility behavior in sharp contrast to polymers exhibiting the same fluorinated side-chain but on every second carbon. 5 In this contribution, we wish to explore another substitution pattern in which two fluorinated side chains are attached on every third carbon on an all carbon-chain backbone (see Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%